Strategies for Strengthening Political Participation of First-Time Voters Through Social Media and Civic Education - Hadi, Ayatullah; Hidayatullah; Alam, Nabil; Pratama, Wahyu; Muliadi, Akmal (Visi Pencerah Nusantara, 2025)
This study examines strategies to enhance political participation among young voters by integrating social media and civic education. This is done in response to the lack of political understanding and high levels of disinformation experienced by the younger generation. Using the Systematic Literature Review (SLR) method, this study examines 184 documents from various scientific sources published between 2019 and 2024 to identify effective strategies for encouraging political participation among young voters. The findings indicate that social media plays a significant role in disseminating political information quickly and engagingly. At the same time, civics education serves to shape character and foster critical and responsible political awareness. The collaboration between social media, civics education, and contributions from families, schools, and youth organizations is considered effective in increasing active, rational, and sustainable political participation. This study proposes enhancing digital political understanding, developing innovative political campaigns, and systematically engaging various parties to cultivate a generation of intelligent and integrity-driven young voters for the future of Indonesian democracy.